Comparison of soccer players` tactical behaviour in small-sided games according to match status - Pinca Badari, T.; Machado, G.; Moniz, F.; Fontes, A.; Teoldo, I. (Journal of Physical Education and Sport, 2021)
Introduction: One way to qualify training and consequently improve players` performance is through comparative analysis by means of contextual variables, such as match status. This type of contextual variable provides information about the players` behaviour according to the different game scenarios. Hence, assessing players' tactical behaviour in SSGs in different match status provides information regarding a context that supports the teaching process in soccer. Objective: This study aimed to compare soccer players` tactical behavioural small-sided games according to match status. Methods: The sample was comprised of 62 U-17 male Brazilian top-level academy players (16.9 ± 0.6 y/o) who compete at national level. In order to establish the match status, the momentary result of a game was considered (winning, losing, or drawing). Players performed 4.988 tactical actions (1030 actions in winning, 2928 actions in drawing, and 1030 actions in losing scenarios). These actions were coded by the System of Tactical Assessment in Soccer (FUT-SAT), which was used to assess players` tactical behaviour based on the core tactical principles of soccer. To line-up teams in a balanced manner, players` game reading and decision-making skills were assessed through the TacticUP® video test for soccer, also based on the core tactical principles of soccer, and the general index provided by the test was used. The comparison between match status was made through the Kruskal-Wallis test. Results: Results indicated that, while winning, players displayed higher tactical behaviour efficiency for the principles of offensive coverage, defensive coverage, as well as higher overall defensive efficiency, compared to the losing match status(p < .05). The comparison of drawing and losing match statuses showed that, when drawing, players displayed higher tactical behaviour efficiency for the overall defensive efficiency (p < .05). Conclusions: We conclude that match status influences the tactical behaviour of U-17 soccer players in small-sided games, based on the core tactical principles. In winning scenarios, players displayed more efficient tactical behaviours, mainly in actions near the ball in both offensive and defensive situations (offensive coverage and defensive coverage principles), as well as higher overall defensive efficiency compared to when they were losing. Moreover, in drawing scenarios, players displayed higher tactical behaviour efficiency for the overall defensive efficiency compared to losing situations. Finally, this study was the first to assess the core tactical principles using complementary instruments (TacticUP® and FUT-SAT) that evaluated both game reading and decision-making skills, as well as tactical behaviour.